GREEN FINANCING PRACTICES WITH SPECIAL EMPHASIS TO INDIAN BANKING INDUSTRY IN INDIA - Prof A.Asif Ali, Prof A.Seshachalam (International Journal of Advanced Science and Technology, 2020)
Banking sectors can afford substantial governance for mandatory fiscal restauration that will provide fresh funding and policy funding opportunities as appropriate as portfolio management to create a formidable, prosperous low-carbon finance system. Green Financing requires mixing effective enhancements, expertise and changes in customer behaviors in financing business.